STUDY OF THE EFFECTS OF EXTERNAL CONDITIONS ON THE PERFORMANCE OF THE "TPG-SN4" METHANE DETECTOR - Olimov Sardor Mustafayevich, Xasanova Gulbahor Raxmatullayevna (Research Focus International Scientific Journal, 2025)
In this article, the influence of external environmental conditions on the operation of the "TPG-CH4" methane gas analyzer was experimentally studied. The main attention was paid to determining the influence of factors such as temperature, humidity, pressure and other gas mixtures on the measurement accuracy and sensitivity. According to the results of the study, when the temperature exceeds +40°C, measurement errors increase to 8–10%, and at high humidity, instability in sensor operation is observed. Also, a decrease in selectivity was determined in the presence of other hydrocarbons. Calibration work, relative and absolute errors, and output signal variability were evaluated according to GOST 13320-81 standards. The results of the study indicate the need for automatic compensation and regular calibration for the effective use of the "TPG-CH4" analyzer in industrial and laboratory conditions.